Pedagogy and Technology (ICT) Integration practices in Science to attain the Learning outcomes. - Eswaran, K. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The Main aims of the teaching and study of sciences are to encourage and enable students to develop scientific attitude, scientific thinking and curiosity about science and the nature. Acquire knowledge, conceptual understanding and science process skills to solve problems and make informed decisions in scientific and other contexts.